PROBING AND IDENTIFYING NEW PHYSICS SCENARIOS AT INTERNATIONAL LINEAR COLLIDER - Pankov, A. A.; Tsytrinov, A. V. (Одеські астрономічні публікації, 2016)
Many new physics scenarios are described bycontact-like eﬀective interactions that can manifest themselves in e+e− collisions through deviations of the observables from the Standard Model predictions. If such a deviation were observed, it would be important to identify the actual source among the possible non-standard interactions as many diﬀerent new physics scenarios may lead to very similar experimental signatures. Here we study the possibility of uniquely identifying the indirect eﬀects of s-channels neutrino exchange with double polarization asymmetry, as predicted by supersymmetric theories with R-parity violation, against other new physics scenarios in process e+e− → µ+µ− at the International Linear Collider.